Exploration of Teachers' Perspectives on The Integration of Environmental Education in Science Learning - R. Didi Kuswara; Ahmad Fadli; Marham Jupri Hadi; Sahratullah Sahratullah; Denda Piki Loli; Haerunnisa Rahmani (Postgraduate, University of Mataram, 2025)
This study aims to reveal the forms of environmental education integration in science learning and the challenges faced by teachers in its implementation. This reseach approach used is a qualitative with a phenomenological design, stages include four main steps, namely bracketing, intuition, analysis, and description. Based on the analysis of teachers' responses, three main forms of integration were obtained, namely. (1) a contextual learning approach, (2) utilizing the surrounding environment, both the school environment and conservation areas, (3) strengthening environmental literacy and awareness through student involvement in environmental management activities. This study also found various challenges in implementing, including limited facilities and infrastructure, low student learning motivation, and difficulties in managing learning activities outside the classroom. External factors, such as limited school support, logistics, weather conditions, and a lack of learning media, exacerbate these obstacles. These findings indicate that teachers have a high awareness of their strategic role in fostering students' ecological awareness. However, in addition, teachers' limited understanding of the concept of environmental education integration in science learning is still found. Therefore, increasing teacher capacity through training, curriculum development, and structural support is important for the successful integration of environmental education in science learning